2022
DOI: 10.2147/copd.s377226
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin/HIF2α-Mediated Ferroptosis is Involved in Skeletal Muscle Dysfunction in Chronic Obstructive Pulmonary Disease

Abstract: Objective Skeletal muscle dysfunction is an important comorbidity in patients with chronic obstructive pulmonary disease (COPD), and is associated with poor quality of life and reduced survival, but the mechanisms involved remain elusive. Ferroptosis is a newly discovered type of cell death resulting from iron‐dependent lipid peroxide accumulation. The purpose of this study was to examine whether ferroptosis is involved in COPD-associated skeletal muscle dysfunction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, several studies have found an increased lipofuscin accumulation in COPD quadriceps [ 126 ] and higher levels of hydroxy-2-nonenal (4-HNE) in quadriceps tissue [ 87 , 127 ], as well as in cultured myotubes from COPD patients [ 128 ]. Ferroptosis, a newly discovered type of cell death resulting from iron-dependent lipid peroxide accumulation, has been reported to be increased both in vitro in CS-exposed C2C12 myotubes and in vivo in a mouse model of COPD [ 129 ]. Finally, nitrosative stress is also increased, as evidenced by higher tyrosine nitration levels in the quadriceps from COPD patients compared to those from healthy subjects [ 122 ], as well as inducible nitric oxide synthase and 3-nitrotyrosine levels [ 127 ].…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…For example, several studies have found an increased lipofuscin accumulation in COPD quadriceps [ 126 ] and higher levels of hydroxy-2-nonenal (4-HNE) in quadriceps tissue [ 87 , 127 ], as well as in cultured myotubes from COPD patients [ 128 ]. Ferroptosis, a newly discovered type of cell death resulting from iron-dependent lipid peroxide accumulation, has been reported to be increased both in vitro in CS-exposed C2C12 myotubes and in vivo in a mouse model of COPD [ 129 ]. Finally, nitrosative stress is also increased, as evidenced by higher tyrosine nitration levels in the quadriceps from COPD patients compared to those from healthy subjects [ 122 ], as well as inducible nitric oxide synthase and 3-nitrotyrosine levels [ 127 ].…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…However, iron supplements, nutritional supplements or iron-rich diets should be utilized with caution because they are likely to be detrimental, as iron may increase ROS and ferroptosis. In particular, ferroptosis has been demonstrated to be involved in the pathogenesis of COPD-related skeletal muscle dysfunction (69). Iron levels of COPD patients should be determined, and according to their levels, patients should be supplemented with iron as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In retinal pigment epithelium cells, stabilized by the 3%O 2 hypoxia condition and PHD inhibitor dimethyloxalylglycine (DMOG) treatment, HIF aggravates sodium iodate-induced ferroptosis by upregulating superoxide dismutase ( SOD ) to execute a peroxidative rather than antioxidative role, as well as increasing the iron importers ZIP8 and ZIP14 to enhance iron import [ 132 ]. Moreover, HIF-2α was found to be upregulated by myostatin in response to cigarette smoke exposure, leading to ferroptosis in myotubes and chronic obstructive pulmonary disease-related skeletal muscle dysfunction [ 133 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%